Exploring Untargeted metabolomics for halal authentication of Triceps brachii, Longissimus Dorsi, and Biceps femoris of meat muscles - Vevi Maritha; Putri Widyanti Harlina; Ida Musfiroh; Mohamad Rafi; Fang Geng; Muchtaridi Muchtaridi (International Journal of Food Properties, 2023)
ABSTRACTThe demand for authentic meat has increased due to the growing consumption of halal meat. In this study, a combined metabolomics and chemometrics approach was employed to authenticate beef and pork samples from specific muscle groups. By using an untargeted metabolomics analysis, distinct metabolite profiles were observed in TB, LD, and BF muscles, differentiating pork from beef. Subsequently, Principal Component Analysis (PCA) results confirmed the distinguishable metabolite profiles between beef and pork. Cluster analysis further revealed that the metabolites in each muscle of beef and pork have different characteristics. Additionally, Partial Least Squares-Discriminant Analysis identified 15 potential metabolites could be used to authenticate the halal status of meat. Creatine, L-carnitine, carnosine, nicotinamide, L-phenylalanine, DL-lactic acid, acetyl L-carnitine, hypoxanthine, inosine, DL-malic acid, N-methyl-2-pyrrolidone, L-glutathione, Inosine-5-monophosphate (IMP), L-tyrosine, and palmitoylcarnitine is a potential metabolite to differentiate beef and pork. This study offers valuable insights into determining the halal status of meat based on metabolite profiles.